Regional structural change and growth in Romania - Iulia Traistaru; Anna Iara; Carmen Pauna (European Regional Science Association (ERSA), 2002)
This paper identifies and explains the impact of increasing economic integration with the European Union on regional structural change and growth in Romania. Using data on imports and exports we first investigate the trade performance patterns between Romania and the European Union in the period 1990-2000. Second, using regional data for the period 1991-1999, we analyse the changes in regional specialisation patterns. Third, we discuss changes in the patterns of location and concentration of industrial activities. Forth, we investigate the relationship between regional specialisation and growth. Next, we look at the role of trade liberalisation in determing regional wage differentials. Finally, based on the results found in the previous sections, this paper predicts the types of likely winning and losing regions in Romania in its economic integration with the European Union.
Keywords: 330